Developing an instrument to measure students’ technopreneurship skill levels in starting new businesses using the rasch model - Mashudi, Imam; Darman, Darman; Djafri, Novianty (International Journal of Innovative Research and Scientific Studies, 2025)
The rapidly evolving digital economy and Industry 4.0 have heightened the demand for graduates equipped with technopreneurship skills, which combine entrepreneurial capabilities with technological innovation. Although entrepreneurship programs are widespread within higher education institutions, there are few well-established tools available to accurately measure students’ specific knowledge types. This study addresses this gap by developing and validating an instrument designed to assess the technopreneurship skills of university students, focusing on dimensions such as opportunity recognition, digital competence, innovation, risk management, and leadership. A research and development (R&D) model was employed to create the instrument, based on the McMillan and Schumacher framework. The study involved 207 undergraduate students from two universities in Gorontalo, Indonesia. A structured Likert-scale questionnaire was designed and finalized through expert validity judgment, followed by validation using Rasch Model analysis. The results demonstrated strong psychometric properties, including a person reliability of 0.87, item reliability of 0.80, a person separation index of 2.56, and an item separation index of 2.02. INFIT and OUTFIT statistics approached 1.00, indicating that the model conformed well to student responses without significant deviations, and no problematic misfitting items were identified. The findings validate the instrument’s reliability and effectiveness in categorizing students into distinct ability groups. This research contributes to the existing body of knowledge by moving beyond perception-based assessments to a formal, empirically grounded method for evaluating technopreneurship competence. Such tools are essential for accurately measuring and fostering entrepreneurial skills in the context of technological advancements, ultimately supporting the development of a workforce capable of thriving in the digital economy.